1993
DOI: 10.1002/art.1780360812
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum levels of soluble tumor necrosis factor receptor and disease activity in systemic lupus erythematosus

Abstract: Objective. To determine the value of measurement of serum soluble tumor necrosis factor receptor (sTNFR), compared with established parameters such as anti-double-stranded DNA, in monitoring systemic lupus erythematosus (SLE) disease activity, and to determine whether serum sTNFR are bioactive and can effectively inhibit TNF bioactivity .Methods. Fifty-three consecutive ambulatory or hospitalized SLE patients and 140 consecutive healthy subjects were enrolled in a prospective cohort study. Serum levels of sTNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(104 citation statements)
references
References 39 publications
11
91
2
Order By: Relevance
“…17 High levels of proinflammatory cytokines have been reported in inflammatory and infectious diseases and can be correlated with disease severity. 32,33 In this study, we did not find any other clinical illness that could explain the high levels of proinflammatory cytokines. On the other hand, our study population was small and, therefore, confounding factors could not be taken into account.…”
Section: Discussioncontrasting
confidence: 57%
“…17 High levels of proinflammatory cytokines have been reported in inflammatory and infectious diseases and can be correlated with disease severity. 32,33 In this study, we did not find any other clinical illness that could explain the high levels of proinflammatory cytokines. On the other hand, our study population was small and, therefore, confounding factors could not be taken into account.…”
Section: Discussioncontrasting
confidence: 57%
“…The association between decreased HDL cholesterol levels and active disease was not surprising, since decreased HDL levels have been reported to be part of the acute-phase response (44), and it has been suggested that high levels of tumor necrosis factor ␣ present in patients with SLE were associated with a lowering of HDL cholesterol levels (28,(45)(46)(47). In years 1-3, only 1 patient had a HDL cholesterol level below that of the age-and sex-matched controls, and the mean values were not significantly different from those in the controls.…”
Section: Sarkissian Et Almentioning
confidence: 99%
“…sTNF-R exists in two different forms, type I (p55) and type II (p75), isolated from either urine or sera, from both healthy donors and cancer patients (9). These proteins function as inhibitors of TNF␣ activity (10).…”
mentioning
confidence: 99%